Global environmental changes: Plants, animals and communities - Graves, Jonathan (Longman, 1996)
The book identifies implications of global environmental change for plants, animals and biological communities. It explains basics of how environmental chnge affects biological processes in a wide range of fields as diverse as cell biology, genetics, physiology and ecology. As well as providing a comprehensive introduction to the subject, a clear and impartial approach is taken on the present and future effects of environmetal changes aupported by results taken from latest scientific investigations